Incidence and mortality of hospital-acquired bacteraemia: a population-based cohort study applying a multi-state model approach. (June 2022) - Mortensen, Viggo Holten; Søgaard, Mette; Mygind, Lone Hagens; Wolkewitz, Martin; Kristensen, Brian; Schønheyder, Henrik Carl
Abstract: Objective: The effect of hospital-acquired bacteraemia on mortality is sparsely investigated. We investigated the incidence and hospital-acquired bacteraemia impact on mortality. Methods: We conducted a 13-year population-based cohort study using the North Denmark Bacteraemia Research Database and Danish health registries. The population comprised all adult patients with a hospital admission lasting ≥48 hr. We used Poisson regression to estimate trends in incidence. The 30-day mortality of hospital-acquired bacteraemia was estimated using an illness-death multistate model with recovery using the population at risk of hospital-acquired bacteraemia as reference. Results: We identified 3588 episodes of hospital-acquired bacteraemia in 484 264 admissions. The incidence increased proportionally by 1.02 episodes yearly (95% CI 1.01–1.03) between 2006 and 2018. Hospital-acquired bacteraemia was associated with increased mortality (adjusted hazard ratio (aHR) 4.32, 95% CI 3.95–4.72), especially hospital-acquired bacteraemia with unknown source (aHR 6.42 (95% CI 5.67–7.26), "thoracic incl. pneumonia" (aHR 5.89, 95% CI 3.45–10.12) and abdominal source (aHR 4.33, 95% CI 3.27–5.74). The relative impact on mortality diminished with age (aHR 5.66, 95% CI 2.00–16.01 in 18–40 years old vs. 3.69, 95% CI 3.14–4.32 in 81–105 years old) and comorbidity (aHR 5.75, 95% CI 4.45–7.42 in low vs. 3.55, 95% CI 3.16–3.98 in high comorbidity), and was higher in elective admissions (aHR 9.09, 95% CI 7.14–11.57 vs. aHR of 4.03, 95% CI 3.67–4.42). Discussion: Hospital-acquired bacteraemia is associated with high mortality, especially when the source is unknown or originating from the thoracic cavity.